Pembinaan Masyarakat Desa Pandesari Malang Melalui Usaha 0lah Limbah Organik Secara Mikrobial - Sudarma Dita Wijayanti; Endrika Widyastuti; Dego Yusa Ali; Ali Wafa (IKIP PGRI Bojonegoro, 2018)
ABSTRACTPandesari Village is a village located in the Pujon District, Malang Regency, East Java Province. The agricultural sector with vegetable commodities and dairy farming are business field that dominates the livelihoods of the people in Pandesari Village, so that the potential for organic waste in the form of vegetable waste and cow dung is very high. However, waste management has not been optimal. Based on these problems, a community empowerment system is needed through microbial organic waste processing. The program involved two partners there are Mekarsari VI Farmers Group Gesingan village as the main supplier of agricultural and livestock waste and Pandesari Village Youth Organization as the second partner. The mechanism for the implementation of this service is implemented by adopting a pattern of action research implementation that includes four stages, there are: program planning, program implementation, observation, and reflection. Based on the results, there was an increase in the level of understanding of trainees regarding the principles of making and application of Local Microorganism (LM) in the growing media and organic animal feed. Assistance related to waste management in Pandesari Village has been carried out so that the village can be more independent to manage and process the waste. Labeling and packaging for LM and products from the use of LM, for example in the form of liquid fertilizer, compost, livestock probiotics which are the results of the production of the Village have been carried out but temporarily used for themselves. Keywords : Microbial, Organic, Waste ABSTRAKDesa Pandesari merupakan desa yang terletak di wilayah Kecamatan Pujon, Kabupaten Malang, Propinsi Jawa Timur. Sektor pertanian dengan komoditas sayuran dan peternakan sapi perah merupakan bidang usaha yang mendominasi mata pencaharian penduduk di Desa Pandesari, sehingga potensi limbah organik berupa sampah sayuran dan kotoran sapi sangat tinggi. Kendati demikian pengolahan limbah belum optimal. Berdasarkan permasalahan tersebut diperlukan sebuah sistem pemberdayaan masyarakat melalui usaha olah limbah organik secara mikrobial. Program ini melibatkan dua mitra yaitu Mitra I adalah Kelompok Tani Mekarsari VI Dusun Gesingan sebagai pemasok utama limbah pertanian dan peternakan dan Mitra II adalah Kelompok Karang Taruna Desa Pandesari. Mekanisme pelaksanaan kegiatan pengabdian ini diimplementasikan dengan mengadopsi pola pelaksanaan penelitian tindakan meliputi empat tahap, yaitu: perencanaan program, pelaksanaan program, observasi, dan refleksi. Berdasarkan capaian yang telah dihasilkan, terjadi peningkatan tingkat pemahaman peserta pelatihan terkait prinsip pembuatan dan aplikasi MOL (Mikroorganisme Lokal) pada media tanam dan pakan ternak organik. Pendampingan terkait manajemen kelola sampah di Desa Pandesari telah dilakukan sehingga desa dapat lebih mandiri untu mengelola dan mengolah sampah. Pembuatan label dan kemasan untuk MOL dan produk hasil penggunaan MOL misalnya berupa pupuk cair, kompos, probiotik ternak yang merupakan hasil produksi Desa telah dilakukan namun sementara digunakan untuk kalangan sendiri. Kata Kunci: Limbah, Mikrobial, Organik